THE COST OF SMS REMINDER TO IMPROVE ARV ADHERENCE AMONG KEY POPULATIONS - Juwita, Mery Nurma; Donny Hardiawan; Prawinegara, Rozar; Handayani, Miasari; Wisaksana, Rudi; Januraga, Pande Putu; Sulaiman, Nurjannah; Siregar, Adiatma (Universitas Airlangga, 2024)
Background: HATI is an implementation trial aimed at improving HIV care and treatment, including through SMS reminders. Aims: This study aimed to estimate the cost and analyze the outcomes of providing SMS Reminders within the HATI program in different settings. Methods: Data were analyzed using a micro-costing approach from providers' and health systems' perspectives. Subjects were divided into intervention and control groups for outcome analysis, with adherence as the outcome indicator. Results: From a provider's perspective, the highest cost was incurred in primary health care (PHC) clinics, while the lowest was in hospital clinics, most likely due to a much higher volume of SMS sent from hospitals. Costs from the health system perspective were more than two times higher than those from the provider perspective, as they included costs borne by HATI management and intervention setup. In one year, the number of patients with >95% adherent visits was higher in the intervention group than the control group, although visits decreased over time in both groups. The highest number of patients with >95% adherent visits was found in PHC clinics, while the lowest was in hospital clinics. Conclusion: SMS reminders can be expensive initially due to setup and program costs. However, they become cheaper once they are embedded into the existing system. Further studies are necessary to determine better site options for scaling up SMS reminder intervention and to study the declining adherence rate in all clinics. Keywords: Adherence, cost analysis, HIV, Indonesia, SMS reminder